Reliability of ankle brachial index in patients with neurological deficits on ischemic episode of the limbs following Burgers exercises: open labelled clinical trial - B. R., Ganesh; Kothiwale, V. A. (International Journal of Research in Medical Sciences, 2017)
Background: Peripheral arterial disease (PAD) is associated with significant morbidity and mortality and is an important marker of subclinical coronary heart disease. In some studies it has been found that surgical intervention alone or physical training alone does not provide good results. Aim of the study was to assess the reliability of ankle brachial index in patients with neurological deficits on ischemic episode of limbs following Burgers exercises. Methods: It was an open labelled clinical trial. Total 35 patients of both male and females were included in this open labelled clinical trial. Two measuring technique ABI and VAS, one exercise program, unsupervised home exercise program and patients advice was part of procedure. Intervention was given at 1st day, 3rd month and 6th month. Results: The study proves that VAS, ABI showed statistical significant difference when analyzed between 1st day to 3rd month, 1st day to 6th month and 3rd month to 6th month with ‛ p ’ value <0.0001. Conclusions: Physical therapy in the form of Burger’s exercise with life style modification is significant in improving quality of life in the form of reducing severity of claudication pain and improving walking distance. Therefore the present study concludes that ABI is a reliable, simple, safe and standard gold diagnostic tool in assessing ischemic episode of the limbs in patients with neurological deficits following burgers exercises.